Dual source computed tomography based analysis of stent performance, its association with valvular calcification and residual aortic regurgitation after implantation of a balloon-expandable transcatheter heart valve - Gerstmeyer, Julius; Kuetting, Maximilian; Fujita, Buntaro; Schuhbaeck, Annika; Boergermann, Jochen; Achenbach, Stephan; Steinseifer, Ulrich; Gummert, Jan; Ensminger, Stephan; Arnold, Martin (Interactive Cardiovascular and Thoracic Surgery, 2017)
Objectives: The aim of this study was to investigate the mutual influence of valvular calcifications and transcatheter aortic valve stent geometry during and after implantation of a balloon-expandable SAPIEN ® /SAPIEN XT ® prostheses. Aortic valve calcification has been linked with adverse complications after transcatheter aortic valve implantation (TAVI). However, little is known about the fate of the calcifications after TAVI as well as its influence on transcatheter heart valve geometry. Methods: Thirty one patients underwent cardiac dual source computed tomography (DSCT) before and after a TAVI with the Edwards SAPIEN/SAPIEN XT ® prostheses. Detailed DSCT image analysis was performed with Mimics ® and 3Matic ® (both Materialise, Leuven, Belgium). Results: Implanted stents reached an average degree of expansion of 84% and achieved good circularity despite the presence of fairly oval native annuli and a heterogeneous degree of valvular calcification. Both, the degree of stent expansion and the degree of stent eccentricity were inversely related to the degree of oversizing, but independent of the degree of valvular calcification and native annular ovality. Visualization of the position of calcific debris before and after TAVI showed that calcifications were shifted upwards and outwards as a consequence of the implantation procedure. The degree of stent eccentricity was related to residual aortic regurgitation grade ≥2. Conclusions: The SAPIEN ® /SAPIEN XT ® prostheses achieved good degrees of stent expansion and circularity regardless of the morphology of the landing zone. Increased stent ovality was associated with an elevated risk for aortic regurgitation. The total calcification volume, degree of annular ovality and stent expansion were not associated with residual AR.
EVALuna2:33643